2005
DOI: 10.1080/00140130512331332891
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric criteria for the design of tractor cabs and protection frames

Abstract: Improved human-tractor interface designs, such as well-accommodated operator enclosures (i.e. cabs and protection frames) can enhance operator productivity, comfort and safety. This study investigated farm-worker anthropometry and determined the critical anthropometric measures and 3-D feature envelopes of body landmarks for the design of tractor operator enclosures. One hundred agriculture workers participated in the study. Their body size and shape information was registered, using a 3-D full-body laser scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 13 publications
0
34
0
1
Order By: Relevance
“…A 95% accommodation level was then selected as this threshold was found to sufficiently balance cab efficiency and cost-effectiveness. This approach resolved the problem of the univariate approach for multiple measurements by taking into account both the overall body size variance and body segment proportional variability (Hsiao et al, 2005;Zehner, Meindl, & Hudson, 1993). The models generated in this study therefore include not only overall large and small persons but also individuals of different body configurations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 95% accommodation level was then selected as this threshold was found to sufficiently balance cab efficiency and cost-effectiveness. This approach resolved the problem of the univariate approach for multiple measurements by taking into account both the overall body size variance and body segment proportional variability (Hsiao et al, 2005;Zehner, Meindl, & Hudson, 1993). The models generated in this study therefore include not only overall large and small persons but also individuals of different body configurations.…”
Section: Discussionmentioning
confidence: 99%
“…The intent was to remove known noisy variables and to reduce data sets to a more manageable size while better addressing equipment accommodation (Bittner, Glenn, Harris, Iavecchia, & Wherry, 1987;Meindl, Zehner, & Hudson, 1993). Principal component analysis (PCA) has been the premier method of variable reduction and has been effective in increasing body size accommodation in tractor cab and cockpit designs (Hsiao et al, 2005;Robinson, Robinette, & Zehner, 1992); it however was found lacking when applied to body dimensions, which showed poor intercorrelation, such as facial dimensions (Hudson, Zehner, & Meindl, 1998).…”
Section: The State Of Anthropometric Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…They checked the location of controls against anthropometrical data. Other example is the research of [16] that found that the SAE 1994 standard for tractors, does not meet anthropometric requirements for manual hand reach. Other studies, such as the study of [24], checked the best location of the pedals in a tractor, in relation to the human strength needed for their operation.…”
Section: Anthropometric Study Of the Cabin Workplacementioning
confidence: 99%
“…Traditional ergonomics evaluation process involve full-size physical mock-up, selection of a representative sample of potential users for executing a series of appropriate human factors evaluations and it is also time consuming, reactive, incomplete, sporadic, and in many cases difficult, too [3]. Although it is well understood that use of scientific and technological advancements will improve the quality as well as productivity with less time and cost but the use of traditional approach of ergonomic evaluation is still in practice for improvement of existing designs of farm tools and implements [4][5][6][7][8][9] Need of virtual ergonomics evaluation techniques in agriculture: Virtual designing and evaluation technology is now widely accepted as a major breakthrough in scientific and technological advancement which leads new possibilities to solve intricate problems, not only in engineering but also in other applied areas including agricultural sector. Need for implementation of virtual ergonomics evaluation technology in agriculture can be perceived by recognizing the problems associated with traditional methods for design, development and ergonomic evaluation.…”
Section: Conventional Ergonomics Approach In Agriculturementioning
confidence: 99%